Ukraine : Soil Fertility to Strengthen Climate Resilience - Fileccia, Turi; Guadagni, Maurizio; Hovhera, Vasyl; Bernoux, Martial (World Bank, Washington, DC and FAO, Rome, 2014)
Ukraine is renowned as the breadbasket of Europe thanks to its black soils ( Chernozem black because of the high organic matter content) which offer exceptional agronomic conditions. One-third of the worldwide stock of the fertile black soils, which cover more than half of Ukraine s arable land, a large variety of climatic zones, and favourable temperature and moisture regimes, offers attractive conditions for the production of a large range of crops including cereals and oilseeds. Ukraine s proximity to large and growing neighbouring markets the Russian Federation and the European Union and access to deep sea ports at the Black Sea, provide direct access to world markets, especially large grain importers in the Middle East and North Africa.